Pertanggungjawaban Pidana Terhadap Pelaku Eksibisionisme - Delton Geisberth Jaranmassa; John Dirk Pasalbessy; Denny Latumaerissa (TATOHI: Jurnal Ilmu Hukum, 2023)
Introduction: In the development of modern times there are many changes that occur, both in technology, crime, even due to sexual deviation, in the Criminal Code in article 281 it reads that whoever intentionally and in front of other people who are there against his will violates decency. They are threatened with imprisonment for a maximum of two years and eight months, but in reality there are cases of crimes against decency, namely exhibitionism, which are not subject to punishment or acquittal.Purposes of the Research:  The purpose of this research is to study and analyze exhibitionism acts that can be qualified as pornographic acts and to analyze the criminal liability of exhibitionism acts.Methods of the Research: The research method in this study is normative legal research, using a law approach, a case approach related to this research.Results of the Research: Based on research results. Exhibitionism can be qualified as action porn because the act of exhibitionism fulfills the elements of action porn where the act is carried out in a public place not through the media, so that exhibitionism acts are classified as a crime of decency but exhibitionism acts cannot be held criminally accountable, some can indeed be punished and there are also those who cannot be held criminally responsible because they fulfill the elements of article 44 of the Criminal Code, in which anyone who commits an act that cannot be held accountable to him because his soul is disabled in growth or disturbed by disease cannot be punished.